Objectively measured levels of moderate to vigorous intensity physical activity are associated with cognitive impairment in diabetic hemodialysis patients: a cross-sectional study - Zhang, Zhixin; Chen, Xiaoyu; Gaowa, Siqin; Liang, Ruiting; Jin, Zhetong; Shi, Ziyi; Han, Peipei; Lin, Cheng; Wen, Xiaoli; Lin, Peng; Guo, Qi (Frontiers in Medicine, 2024)
The purpose of this study was to observe the relationship between objectively measured levels of physical activity and cognitive impairment (CI) in the presence or absence of diabetes in middle-aged and elderly hemodialysis patients.: In this multicenter cross-sectional study, 339 clinically stable hemodialysis patients (210 males; mean age: 67.38±8.07 years) aged ≥55 years were included from 7 dialysis units in Shanghai, China. The Chinese version of the Modified Mini-Mental State Examination (MMSE) was used to assess the CI. The duration of physical activity at different intensities, including moderate to vigorous physical activity (MVPA) as well as light physical activity (LPA), was measured using a triaxial accelerometer (ActiGraph GT3X+, Pensacola, FL, USA). Logistic regression and multiple linear regression were used for analyses.Results: The prevalence of CI was higher in hemodialysis patients with comorbid diabetes (24.3%).In diabetic patients, MVPA (increase per 10min/day) was negatively associated with CI after adjusting for covariates [(OR=0.89, 95%CI=0.79-0.99), P=0.042]. However, no significant association between physical activity and CI was found in non-diabetic hemodialysis patients.Further analyses revealed that MVPA was positively associated with temporal orientation, attention and calculation and recall in diabetic hemodialysis patients.Physical activity was associated with CI in diabetic hemodialysis patients rather than the non-diabetes group. This study is important for early differential diagnosis of CI and improvement of cognitive status in hemodialysis patients.